A Case Report of Maxillary Second Molar with Two Palatal Root Canals and a Furcal Enamel Pearl - Shojaeian, Shiva; Ghoddusi, Jamileh; Hajian, Sara (Iranian Endodontic Journal, 2013)
This case report presents an uncommon case of maxillary molar with two palatal root canals and an enamel pearl in the furcation area. The article discusses root canal complexities of maxillary second molars as well as possibility of coexisting anomalies in the region that makes radiographic interpretation difficult and compromises the success of endodontic treatment.